Creación de una microempresa productora y comercializadora de Snack´s de plátano con omega 3, fortificado con vitamina C y vitamina A en diferentes sabores en la ciudad de Pereira (Risaralda) (2015)
The project that I'm going to present is a business initiative, which arises because of the bond we've had in the business of distribution of agricultural products "Banana" 2 years ago, with the aim of creating a business plan, for the production and marketing of chip-based banana made with Omega 3 oil and Fortified with flavors of vitamin A and C. In our country the snack consumption is high (the Republic Delgado, 2013), since it is a food that becomes part of the family shopping basket and has become essential in the culture of the country, because it tends to accompany all kinds of events, its consumption does not discriminate sex, age or social stratum. Colombia with a consumption per capita 2.6/Kg, is third in Latin America, after Mexico with 3.8 kilos and Chile with 2.7 (time T. e., 2013). The Eje Cafetero region shows tremendous growth in the banana; It is a product that can be processed for different purposes and thus generate value in your supply chain, Therefore, the decision for the creation of this company located in the industrial area of the city of Pereira, that facilitates physical distribution and its proximity to the raw, working with a team that has five years of experience in the sector of fried foods. The investment total to a realization of the project is $147.869.500. Provides 56,21% with own resources. It is expected to get credits by 43.79%. The investment is spent for working capital 3.38% and fixed assets 96,62%. Is look for sources or funds for the financing of the business plan, in support to projects of entrepreneurs organizations as Fund launch (fondo emprender). That supports business initiatives to professionals or students who have ninth semester and carrying not more than two years of graduating.